1998
DOI: 10.1039/a805617j
|View full text |Cite
|
Sign up to set email alerts
|

Residues and metabolism of 19-nortestosterone laurate in steers†

Abstract: The illegal use of nandrolone) and its esters in livestock, for growth promotion purposes, has been widely reported in the European Union. The target residues for surveillance of abuse in bovine urine and bile samples are 17a-and 17b-19NT, although this choice of target residues is not based on in vivo radiotracer biotransformation data. In this study, four steers were administered [ 3 H 2 ]-and [ 2 H 3 ] 17b-19NT laurate (2 mg kg 21 body mass) by intramuscular injection and blood, urine, faeces and bile sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In a previous study, nonoxidative glucose metabolism and glycogenolysis were observed to increase with hyperthyroidism. 37 The authors suggest that this was caused by a perturbation in energy metabolism, leading to increased levels of inorganic phosphate, which would stimulate glycogen metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, nonoxidative glucose metabolism and glycogenolysis were observed to increase with hyperthyroidism. 37 The authors suggest that this was caused by a perturbation in energy metabolism, leading to increased levels of inorganic phosphate, which would stimulate glycogen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, nonoxidative glucose metabolism and glycogenolysis were observed to increase with hyperthyroidism. 37 The authors suggest that this was caused by a perturbation in energy metabolism, leading to increased levels of inorganic phosphate, which would stimulate glycogen metabolism.We also found evidence of increased anaplerotic processing of pyruvate, a mechanism by which carbon flux into the Krebs cycle can be maintained under conditions of reduced PDH flux. We have been able to identify and quantify an MRS resonance corresponding to [3-13 C]citrate, the formation of which has not previously been observed in vivo, in real time.…”
mentioning
confidence: 99%
“…19-Nortestosterone (19-NT) was synthesized for the first time by Birch in 1950 and by Wilds andNelson in 1953 (Le Bizec et al, 2002;Kohler and Lambert, 2002), which is designed for treatments of a wide span of haematological, post surgical conditions, cachexia, and substitutive progestin supplementation, and is also used in veterinary as well as human medicine in case of protein deficiency, breast cancer, osteoporosis, or burns (Delbeke et al, 1995;Sauer et al, 1998;Bricout and Wright, 2004;Chen et al, 2004). In animal husbandry, 19-NT can enhance lean tissue growth, reduce fat deposition, increase the weight gain, and feed conversion efficiency (Roda et al, 2003;Conneely et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…193 of the Ministry of Agriculture in April 2002). However, illegal use of NT as a growth promoter has been widely reported throughout Europe [2] and in China, thus prompting continuous surveillance to control its abuse.…”
mentioning
confidence: 99%
“…In the 1950s, the recognition of the growth promoting property of NT led to it being used to accelerate meat production. It can enhance lean tissue growth, reduce fat deposition, increase the weight gain and feed conversion efficiency of animals [2][3][4]. Administration is usually by intramuscular injection of the esterified drug in suspension with benzyl alcohol and arachis oil, or inserted into the fleshy part of the ear.…”
mentioning
confidence: 99%